1998
DOI: 10.1111/j.1151-2916.1998.tb02316.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Determination of the Gibbs Energy of Formation of MgAl2O4

Abstract: The standard Gibbs energy of formation of the spinel MgAl 2 O 4 from component oxides, MgO and ␣-Al 2 O 3 , has been determined in the temperature range 900 to 1250 K using a solid-state cell incorporating single-crystal CaF 2 as the solid electrolyte. The cell can be represented as The standard Gibbs energy of formation from binary oxides, computed from the reversible emf, can be represented by the expression ⌬G°f ,ox = −23600 − 5.91T (±150) J/mol The ''second-law'' enthalpy of formation of MgAl 2 O 4 obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The ΔGD caused by the cation exchange reaction in the MgAl 2 O 4 -spinel can be evaluated by resorting to the difference of the Gibbs energies of formation of the MgAl 2 O 4 -spinels (ΔGf) at different temperatures. Rosén and Muan [58], Chamberlin et al [59], Jacob et al [60], and Fujii et al [61] determined the values of the Gf at different temperatures using different methods, as summarized in Figure 7a. Fitting these experimental results leads to the following Gf~ T correlation, Gf = −2.613 × 10 −8 × T 3 + 8.159 × 10 −5 × T 2 − 0.090 × T + 5.281.…”
Section: Discussionmentioning
confidence: 99%
“…The ΔGD caused by the cation exchange reaction in the MgAl 2 O 4 -spinel can be evaluated by resorting to the difference of the Gibbs energies of formation of the MgAl 2 O 4 -spinels (ΔGf) at different temperatures. Rosén and Muan [58], Chamberlin et al [59], Jacob et al [60], and Fujii et al [61] determined the values of the Gf at different temperatures using different methods, as summarized in Figure 7a. Fitting these experimental results leads to the following Gf~ T correlation, Gf = −2.613 × 10 −8 × T 3 + 8.159 × 10 −5 × T 2 − 0.090 × T + 5.281.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Gibbs energies of formation of MgAl 2 O 4 from MgO and Al 2 O 3 were measured by several authors [37,[47][48][49][50] using different techniques. Taylor and Schmalzried, [49] and more recently Jacob and Jayadevan, [47] used a MgF 2 electrolyte to measure the Gibbs energy of MgAl 2 O 4 . Chamberlin et al [48] equilibrated spinel and liquid Pd and measured the Mg and Al contents in the Pd.…”
Section: Summary Of Available Experimental Datamentioning
confidence: 99%
“…The data of Taylor and Schmalzried [49] are not in agreement with the data of other authors. Also it was difficult to reproduce the measurements of Jacob and Jayadevan [47] who used emf cells with MgF 2 electrolytes as did Taylor and Schmalzried.…”
Section: Evaluation and Optimizationmentioning
confidence: 99%
“…In their study on NiSn/MgOAl 2 O 3 materials Penkova et al[30] attributed this shift to the formation of magnesium aluminate phase. In this sense Jacob et al[31] also reported that the formation of MgAl 2 O 4 from MgO and Al 2 O 3 could start at around 800 ºC.…”
mentioning
confidence: 94%